2009
DOI: 10.3102/0162373709343964
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Causal Inference From an Observational Study: Results of a Within-Study Comparison

Abstract: Adjustment methods such as propensity scores and analysis of covariance are often used for estimating treatment effects in nonexperimental data. Shadish, Clark, and Steiner used a within-study comparison to test how well these adjustments work in practice. They randomly assigned participating students to a randomized or nonrandomized experiment. Treatment effects were then estimated in the experiment and compared to the adjusted nonexperimental estimates. Most of the selection bias in the nonexperiment was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…PS ϭ propensity score; ANCOVA ϭ analysis of covariance. Pohl, Steiner, Eisermann, Soellner, and Cook (2009) also succeeded in removing all the selection bias in the quasi-experiment despite a different selection mechanism and different degrees of initial bias. Additional analyses of this data set also indicated that proxy-pretest measures and topic preference were once again necessary and sufficient for removing all the selection bias .…”
Section: Discussionmentioning
confidence: 98%
“…PS ϭ propensity score; ANCOVA ϭ analysis of covariance. Pohl, Steiner, Eisermann, Soellner, and Cook (2009) also succeeded in removing all the selection bias in the quasi-experiment despite a different selection mechanism and different degrees of initial bias. Additional analyses of this data set also indicated that proxy-pretest measures and topic preference were once again necessary and sufficient for removing all the selection bias .…”
Section: Discussionmentioning
confidence: 98%
“…Here, we make use of an ANCOVA method (Mayer, Dietzfelbinger, & Rosseel, ; Steyer & Partchev, ) and a PS method (Lockwood & McCaffrey, ) that can incorporate latent covariates for adjustment. We apply these methods, using empirical data from a within‐study comparison (WSC; Pohl, Steiner, Eisermann, Soellner, & Cook, ) and evaluate whether attenuation bias occurs in empirical data. In the following, we first review the theoretical results on attenuation bias and describe the adjustment methods.…”
Section: Impact Of Adjusting For Fallible or Latent Covariates In Pramentioning
confidence: 99%
“…We use the data of a four‐arm WSC conducted by Pohl et al . () and evaluate the accuracy of ATE estimates when we correct for measurement error in covariates in comparison to using fallible covariates for adjustment. In the quasi‐experimental data, the participants self‐selected to the treatment conditions and had no information about the fallible covariates.…”
Section: Impact Of Adjusting For Fallible or Latent Covariates In Pramentioning
confidence: 99%
“…As discussed above, Shadish, Clark, and Steiner (2008) like setting, and short intervention period. Pohl, Steiner, Eisermann, Soellner, and Cook (2009) conducted a replication of the WSC approach used by Shadish et al (2008) Demographic Covariates. In many observational studies, the carefully considered selection process and rich covariate sets exemplified by Shadish et al (2008) and Pohl et al (2009) are the exceptions rather than the rule.…”
Section: Performance Of Local Versus Non-local Comparison Groupsmentioning
confidence: 99%
“…Pohl, Steiner, Eisermann, Soellner, and Cook (2009) conducted a replication of the WSC approach used by Shadish et al (2008) Demographic Covariates. In many observational studies, the carefully considered selection process and rich covariate sets exemplified by Shadish et al (2008) and Pohl et al (2009) are the exceptions rather than the rule. Observational studies often depend on simple predictors of convenience such as race/ethnicity, gender, free-reduced price lunch status, disability status, and gender.…”
Section: Performance Of Local Versus Non-local Comparison Groupsmentioning
confidence: 99%